Surface-enhanced Raman scattering by colloidal CdSe nanocrystal submonolayers fabricated by the Langmuir–Blodgett technique - Milekhin, Alexander G.; Sveshnikova, Larisa L.; Duda, Tatyana A.; Rodyakina, Ekaterina E.; Dzhagan, Volodymyr M.; Gordan, Ovidiu D.; Veber, Sergey L.; Himcinschi, Cameliu; Latyshev, Alexander V.; Zahn, Dietrich R. T. (Beilstein Journal of Nanotechnology, 2015)
We present the results of an investigation of surface-enhanced Raman scattering (SERS) by optical phonons in colloidal CdSe nanocrystals (NCs) homogeneously deposited on both arrays of Au nanoclusters and Au dimers using the Langmuir–Blodgett technique. The coverage of the deposited NCs was less than one monolayer, as determined by transmission and scanning electron microscopy. SERS by optical phonons in CdSe nanocrystals showed a significant enhancement that depends resonantly on the Au nanocluster and dimer size, and thus on the localized surface plasmon resonance (LSPR) energy. The deposition of CdSe nanocrystals on the Au dimer nanocluster arrays enabled us to study the polarization dependence of SERS. The maximal SERS signal was observed for light polarization parallel to the dimer axis. The polarization ratio of the SERS signal parallel and perpendicular to the dimer axis was 20. The SERS signal intensity was also investigated as a function of the distance between nanoclusters in a dimer. Here the maximal SERS enhancement was observed for the minimal distance studied (about 10 nm), confirming the formation of SERS “hot spots”.
Keywords: CdSe nanocrystals; dimers; localized surface plasmon resonance; metal nanoclusters; phonons; surface-enhanced Raman spectroscopy

(untitled) - Fleishman, M.; Hendra, P. J.; McQuillan, A. J. (Chem. Phys. Lett., 1974)

(untitled) - Moskovits, M. (Rev. Mod. Phys., 1985)

Light Scattering in Solids IV - Otto, A. (Surface-enhanced Raman scattering: classical and chemical origins, 1984)

Surface-enhanced vibrational spectroscopy - Aroca, R. (John Wiley & Sons Ltd., 2006)

Surface Enhanced Raman Spectroscopy - Schluecker, S. (Wiley-VCH, 2011)

Principles of surface-enhanced Raman spectroscopy and related plasmonic effects - Le Ru, E.; Etchgoin, P. (Elsevier, 2000)

Surface-Enhanced Raman Scattering, Physics and Applications - Kneipp, K.; Moskovits, M.; Kneipp, H. (Springer-Verlag, 2006)

(untitled) - Kneipp, K.; Wang, Y.; Kneipp, H.; Perelman, L. T.; Itzkan, I.; Dasari, R. R.; Feld, M. S. (Phys. Rev. Lett., 1997)

(untitled) - Nie, S.; Emory, S. R. (Science, 1997)

(untitled) - Camden, J. P.; Dieringer, J. A.; Wang, Y.; Masiello, D. J.; Marks, L. D.; Schatz, G. C.; Van Duyne, R. P. (J. Am. Chem. Soc., 2008)

(untitled) - Alexander, K. D.; Hampton, M. J.; Zhang, S.; Dhawan, A.; Xu, H.; Lopez, R. (J. Raman Spectrosc., 2009)

(untitled) - Kleinman, S. L.; Frontiera, R. R.; Henry, A.-I.; Dieringer, J. A.; Van Duyne, R. P. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Schedin, F.; Lidorikis, E.; Lombardo, A.; Kravets, V. G.; Geim, A. K.; Grigorenko, A. N.; Novoselov, K. S.; Ferrari, A. C. (ACS Nano, 2010)

(untitled) - Lefrant, S.; Baltog, I.; Baibarac, M.; Mevellec, J. Y.; Chauvet, O. (Carbon, 2002)

(untitled) - Kneipp, K.; Kneipp, H.; Corio, P.; Brown, S. D. M.; Shafer, K.; Motz, J.; Perelman, L. T.; Hanlon, E. B.; Marucci, A.; Dresselhaus, G.; Dresselhaus, M. S. (Phys. Rev. Lett., 2000)

(untitled) - Perevedentseva, E.; Karmenyan, A.; Chung, P.-H.; He, Y.-T.; Cheng, C.-L. (Surf. Sci., 2006)

(untitled) - Honma, I.; Sano, T.; Komiyama, H. (J. Phys. Chem., 1993)

(untitled) - Milekhin, A. G.; Yeryukov, N. A.; Sveshnikova, L. L.; Duda, T. A.; Kosolobov, S. S.; Latyshev, A. V.; Surovtsev, N. V.; Adichtchev, S. V.; Himcinschi, C.; Zenkevich, E. I.; Jian, W.-B.; Zahn, D. R. T. (J. Phys. Chem. C, 2012)

(untitled) - Wang, Y.; Li, M.; Jia, H.; Song, W.; Han, X.; Zhang, J.; Yang, B.; Xu, W.; Zhao, B. (Spectrochim. Acta, Part A: Mol. Spectrosc., 2006)

(untitled) - Hugall, J. T.; Baumberg, J. J.; Mahajan, S. (Appl. Phys. Lett., 2009)

(untitled) - Chursanova, M. V.; Dzhagan, V. M.; Yukhymchuk, V. O.; Lytvyn, O. S.; Valakh, M. Ya.; Khodasevich, I. A.; Lehmann, D.; Zahn, D. R. T.; Waurisch, C.; Hickey, S. G. (Nanoscale Res. Lett., 2010)

(untitled) - Lee, Y.-B.; Lee, S. H.; Lee, S.; Lee, H.; Kim, J.; Joo, J. (Appl. Phys. Lett., 2013)

(untitled) - Todescato, F.; Minotto, A.; Signorini, R.; Jasieniak, J. J.; Bozio, R. (ACS Nano, 2013)

(untitled) - Sheremet, E.; Milekhin, A. G.; Rodriguez, R. D.; Weiss, T.; Nesterov, M.; Rodyakina, E. E.; Gordan, O. D.; Sveshnikova, L. L.; Duda, T. A.; Gridchin, V. A.; Dzhagan, V. M.; Hietschold, M.; et al. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Wang, X.; Kong, X.; Yu, Y.; Zhang, H. (J. Phys. Chem. C, 2007)

(untitled) - Liu, C. Y.; Dvoynenko, M. M.; Lai, M. Y.; Chan, T. H.; Lee, Y. R.; Wang, J.-K.; Wang, Y. L. (Appl. Phys. Lett., 2010)

(untitled) - Milekhin, A. G.; Yeryukov, N. A.; Sveshnikova, L. L.; Duda, T. A.; Zenkevich, E. I.; Kosolobov, S. S.; Latyshev, A. V.; Himcinski, C.; Surovtsev, N. V.; Adichtchev, S. V.; Feng, Z. C.; Wu, C. C.; et al. (J. Exp. Theor. Phys., 2011)

(untitled) - Rumyantseva, A.; Kostcheev, S.; Adam, P.-M.; Gaponenko, S. V.; Vaschenko, S. V.; Kulakovich, O. S.; Ramanenka, A. A.; Guzatov, D. V.; Korbutyak, D.; Dzhagan, V.; Stroyuk, A. L.; Shvalagin, V. V. (ACS Nano, 2013)

(untitled) - Milekhin, A. G.; Yeryukov, N. A.; Sveshnikova, L. L.; Duda, T. A.; Rodyakina, E. E.; Sheremet, E. S.; Ludemann, M.; Gordan, O. D.; Latyshev, A. V.; Zahn, D. R. T. (Thin Solid Films, 2013)

(untitled) - Milekhin, A. G.; Yeryukov, N. A.; Sveshnikova, L. L.; Duda, T. A.; Rodyakina, E. E.; Gridchin, V. A.; Sheremet, E. S.; Zahn, D. R. T. (Beilstein J. Nanotechnol., 2015)

Semiconductor nanocrystal quantum dots: synthesis, assembly, spectroscopy, and applications - Rogach, A. (Springer, 2008)

(untitled) - Sigle, D. O.; Hugall, J. T.; Ithurria, S.; Dubertret, B.; Baumberg, J. J. (Phys. Rev. Lett., 2014)

(untitled) - Etchegoin, P. G.; Le Ru, E. C. (Phys. Chem. Chem. Phys., 2008)

(untitled) - Kahl, M.; Voges, E.; Kostrewa, S.; Viets, C.; Hill, W. (Sens. Actuators, B, 1998)

(untitled) - Gunnarsson, L.; Bjerneld, E. J.; Xu, H.; Petronis, S.; Kasemo, B.; Käll, M. (Appl. Phys. Lett., 2001)

(untitled) - Chou, S. Y. (MRS Bull., 2001)

(untitled) - Choi, C. J.; Xu, Z.; Wu, H.-Y.; Liu, G. L.; Cunningham, B. T. (Nanotechnology, 2010)

(untitled) - Hulteen, J. C.; Van Duyne, R. P. (J. Vac. Sci. Technol., A, 1995)

(untitled) - Haynes, C. L.; Van Duyne, R. P. (J. Phys. Chem. B, 2001)

(untitled) - Dabbousi, B. O.; Murray, C. B.; Rubner, M. F.; Bawendi, M. G. (Chem. Mater., 1994)

(untitled) - Cordero, S. R.; Carson, P. J.; Estabrook, R. A.; Strouse, G. F.; Buratto, S. K. (J. Phys. Chem. B, 2000)

(untitled) - Gattás-Asfura, K. M.; Constantine, C. A.; Lynn, M. J.; Thimann, D. A.; Ji, X.; Leblanc, R. M. (J. Am. Chem. Soc., 2005)

(untitled) - Munechika, K.; Chen, Y.; Tillack, A. F.; Kulkarni, A. P.; Plante, I. J.-L.; Munro, A. M.; Ginger, D. S. (Nano Lett., 2010)

(untitled) - Peterson, I. R. (J. Phys. D, 1990)

(untitled) - Dzhagan, V. M.; Valakh, M. Ya.; Raevskaya, A. E.; Stroyuk, A. L.; Kuchmiy, S. Ya.; Zahn, D. R. T. (Nanotechnology, 2007)

(untitled) - Jain, P. K.; Huang, W.; El-Sayed, M. A. (Nano Lett., 2007)

(untitled) - Christensen, N. E.; Seraphin, B. O. (Phys. Rev. B, 1971)

(untitled) - Stiles, P. L.; Dieringer, J. A.; Shah, N. C.; Van Duyne, R. P. (Annu. Rev. Anal. Chem., 2008)

(untitled) - Hwang, Y.-N.; Park, S.-H.; Kim, D. (Phys. Rev. B, 1999)

(untitled) - Baranov, A. V.; Rakovich, Ya. P.; Donegan, J. F.; Perova, T. S.; Moore, R. A.; Talapin, D. V.; Rogach, A. L.; Masumoto, Y.; Nabiev, I. (Phys. Rev. B, 2003)

(untitled) - Baganich, A. A.; Mikla, V. I.; Semak, D. G.; Sokolov, A. P.; Shebanin, A. P. (Phys. Status Solidi B, 1991)

(untitled) - Raevskaya, A. E.; Stroyuk, A. L.; Kuchmiy, S. Ya.; Dzhagan, V. M.; Zahn, D. R. T.; Schulze, S. (Solid State Commun., 2008)

(untitled) - Garcia, M. A. (J. Phys. D: Appl. Phys., 2011)